Comparative Stability Analysis of a Frigate According to the Different Navy Rules in Waves - Kahramanoglu, Emre; Yilmaz, Huseyin; Yildiz, Burak (UNIV STRATHCLYDE, DEPT NAVAL ARCHITECTURE & MARINE ENGINEERING, 2015)
As it is known, the naval ships are vulnerable to be damaged because of their mission. Therefore the most important parameter is survivability for them. This parameter is directly related to damaged stability analysis. In this study, the intact and damaged stability analysis of a frigate which is partially modernized have been carried out in waves according to three different navy rules. In addition to its conformity with these three different groups of rules, it has been examined that whether there are conflicting and varying points of different group of rules with each other and it has been tried to determine which one is more realistic.
Keywords: damage stability; frigate; naval ship stability; LOADS; SHIPS; Engineering